Intergenerational relations and the power of the cell phone: Perspectives on young people's phone usage in sub-Saharan Africa. (August 2015) - Porter, Gina; Hampshire, Kate; Abane, Albert; Munthali, Alister; Robson, Elsbeth; Bango, Andisiwe; de Lannoy, Ariane; Gunguluza, Nwabisa; Tanle, Augustine; Owusu, Samuel; Milner, James
Highlights: We examined youth mobile phone links in 24 sites [Ghana, Malawi, South Africa]. Under 16s communication focuses on relatives and those of a different age-cohort. 16+ youth in South Africa communicate more with extra-family (same-age) friends. 16+ youth communication in urban Ghana and Malawi shows a similar trend. Elders' dependence on youth 'info-mediaries' encourages a generational power-shift. Abstract: Cell phones present new forms of sociality and new possibilities of encounter for young people across the globe. Nowhere is this more evident than in sub-Saharan Africa where the scale of usage, even among the very poor, is remarkable. In this paper we reflect on the inter-generational encounters which are embedded in young people's cell phone interactions, and consider the wider societal implications, not least the potential for associated shifts in the generational balance of power. An intriguing feature of this changing generational nexus is that while many young people's phone-based interactions, from their mid-teens onwards, are shifting away from the older generation towards friendship networks in their own age cohort, at the same time they are repositioning themselves – or becoming repositioned – as family information hubs, as a consequence of their phone expertise. The paper draws on mixed-methods research with young people aged c. 9–25 years and in-depth interviews with older age-groups in 24 sites (ranging from high density poor urban to remote rural) across Ghana, Malawi and South Africa.